2015
DOI: 10.1134/s1021443715030115
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzyme activity and osmolyte content in winter cereal seedlings under hardening and cryostress

Abstract: Activities of antioxidant enzymes and the osmolyte contents in seedlings of winter rye (Secale cereale L.), soft (Triticum aestivum L.) and durum (T. durum L.) wheat, and barley (Hordeum vulgare L.) grown at 20°C (control) or after 7 day cold hardening at 2°C and/or 5 hour freezing at -6°C were investi gated. It was found that nonhardened rye seedlings differed from those of other cereals by their ability to sur vival after freezing at -6°C and higher activity of guaiacol peroxidase (GPO) and high content of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Thus, it has been shown that the basic resistance of rye seedlings to direct agents of oxidative stress (hydrogen peroxide and iron(II) sulfate) was significantly higher than that of bread wheat (Kolupaev et al, 2016). It is well known that rye is more frost resistant than most other cereals (Fu et al, 1998;Kolupaev et al, 2015). Fu et al (1998) associated rye resistance to both low and high temperatures with a significant accumulation of various carbohydrates, including fructans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it has been shown that the basic resistance of rye seedlings to direct agents of oxidative stress (hydrogen peroxide and iron(II) sulfate) was significantly higher than that of bread wheat (Kolupaev et al, 2016). It is well known that rye is more frost resistant than most other cereals (Fu et al, 1998;Kolupaev et al, 2015). Fu et al (1998) associated rye resistance to both low and high temperatures with a significant accumulation of various carbohydrates, including fructans.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of LPO products content. Analysis of the amount of lipid peroxidation (LPO) products reacting with 2-thiobarbituric acid (mainly malonic dialdehyde, MDA) in the shoots was carried out according to the protocol described earlier (Kolupaev et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the hydrolysis of starch is enhanced when the temperature drops to −3°С or −5°С. This leads to the accumulation of sugars, which is an adaptation to hypothermia in winter (Tumanov 1976;Kolupaev and Trunova 1992;Kolupaev et al 2015;Zeng et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, higher activities of CAT and GPX, especially at the advanced time-points of CA, seem to be involved in this phenomenon. Low temperature was proved to increase the activity of SOD and CAT in Hordeum vulgare , S. cereale, Triticum aestivum, and T. durum [ 73 ]. Furthermore, in the other research on T. aestivum it was shown that low temperature increased the activity of SOD, APX, GR, and POD [ 74 ].…”
Section: Discussionmentioning
confidence: 99%